Tourism Development Towards Economic Sustainability of Local Communities in Parangtritis Tourism Area - Hulu, M; Baiquni, M; Fandeli, C; Wirasanti, N (KnE Social Sciences, 2018)
Tourism activities have a negative and positive impact on the community. Increasing local people’s income is one of the positive impacts of tourism activities. This study aims to determine the form of local community participation, economic sustainability of the community who contribute to the development of sustainable tourism in the coastal tourist area of Parangtritis village. Collaboration between community groups that are in direct contact with or not in direct contact with tourism activities remain well established and gain economic benefits from tourism activities in the tourist area of Parangtritis. This research was conducted to both community groups with interview and direct observation techniques. The results of this study indicate that tourism activities in the tourist area Parangtritis provide economic benefits for local communities. Communities in the area of parangtritis have diversified livelihoods, so as to survive in certain situations. For example in fish season, rainy season, dry season and holiday season. Tourists who visit the tourist area of Parangtritis in addition to tourism activities, can also buy crops from local communities that are sold around the tourist area Parangtritis. So that local people get economic benefits related to sustainable tourism activities. Keywords: Sustainable Tourism, Collaborative, Economic Sustainability.